2020
DOI: 10.1056/nejmoa1909512
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Cabotegravir and Rilpivirine after Oral Induction for HIV-1 Infection

Abstract: BACKGROUND Long-acting injectable regimens may simplify therapy for patients with human immunodeficiency virus type 1 (HIV-1) infection. METHODS We conducted a phase 3, randomized, open-label trial in which adults with HIV-1 infection who had not previously received antiretroviral therapy were given 20 weeks of daily oral induction therapy with dolutegravir-abacavir-lamivudine. Participants who had an HIV-1 RNA level of less than 50 copies per milliliter after 16 weeks were randomly assigned (1:1) to continue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
351
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(376 citation statements)
references
References 16 publications
19
351
2
4
Order By: Relevance
“… 12 , 13 Both compounds are formulated as LA agents to be administered intramuscularly (IM), with oral formulations of RPV and a new formulation of CAB in development. 13 These oral formulations have been used during an oral lead-in phase in the ATLAS 14 and FLAIR 15 studies to assess safety and tolerability before study participants transitioning to LA therapy with CAB and RPV. This 2-drug oral combination therapy of CAB and RPV was assessed in the LATTE (NCT01641809) study and shown to provide similar antiviral activity compared with efavirenz plus dual NRTIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 Both compounds are formulated as LA agents to be administered intramuscularly (IM), with oral formulations of RPV and a new formulation of CAB in development. 13 These oral formulations have been used during an oral lead-in phase in the ATLAS 14 and FLAIR 15 studies to assess safety and tolerability before study participants transitioning to LA therapy with CAB and RPV. This 2-drug oral combination therapy of CAB and RPV was assessed in the LATTE (NCT01641809) study and shown to provide similar antiviral activity compared with efavirenz plus dual NRTIs.…”
Section: Introductionmentioning
confidence: 99%
“…ATLAS (NCT02951052) 14 and FLAIR (NCT02938520) 15 are ongoing randomized, open-label, multinational phase 3 studies. These studies demonstrated that monthly injections of CAB + RPV LA were noninferior based on the primary endpoint (participants with plasma HIV-1 RNA ≥50 copies/mL at week 48) compared with a control group who continued their oral current antiretroviral regimen (CAR).…”
Section: Introductionmentioning
confidence: 99%
“…Studies are under way to formulate CPT31 in a depot that could be used in such a context. Additionally, this formulation could be paired with other long-acting drugs, such as nanocrystals of cabotegravir (GSK744; GlaxoSmithKline) and/or rilpivirine (TMC278; Tibotec) ( 19 , 20 ), ibalizumab ( 21 ), or promising antibodies and small-molecule inhibitors (Merck’s islatravir/MK-8591 and Gilead’s GS-6207) in clinical development ( 22 , 23 ). To fully evaluate CPT31’s therapeutic potential, it will be important to evaluate its efficacy when administered with other antiretrovirals to identify optimal combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are underway to formulate CPT31 in a depot that could be used in such a context. Additionally, this formulation could be paired with other long-acting drugs, such as nanocrystals of cabotegravir (GSK744, GlaxoSmithKline) and/or rilpivirine (TMC278, Tibotec) (Orkin et al, 2020; Swindells et al, 2020), ibalizumab (Emu et al, 2018), or promising antibodies and small molecule inhibitors (Merck’s islatravir/MK-8591 and Gilead’s GS-6207) in clinical development (Coelho et al, 2019; Schurmann et al, 2020). To fully evaluate CPT31’s therapeutic potential, it will be important to evaluate its efficacy when administered with other antiretrovirals to identify optimal combinations.…”
Section: Discussionmentioning
confidence: 99%